A Dynamic Analysis of Growth via Acquisition - Margsiri, Worawat; Mello, Antonio S.; Ruckes, Martin E. (Review of Finance, 2008)
Abstract Firms can grow through internal investment or through acquisition. While internal growth takes time, an acquisition provides cash flows immediately. The opportunity to grow internally affects the price of an acquisition as it is a fall-back option for the acquirer should negotiations break down. Assuming investors do not have full information about the time a firm requires to grow internally, acquirers earn positive returns before the announcement of an acquisition, and there are negative stock price reactions to acquisition announcements. This research provides predictions about how pre-announcement price run-up and negative announcement returns relate to integration costs and synergies from acquisition.